(untitled) (Medical Forum Monthly, 2024)
Objectives: Since suicide is increasing in Pakistan and has become a major Public problem, the objective of our study is Analysis of the different methods used for suicide, most vulnerable persons from point of view of factors responsible for suicide ideation and commission. Finally to suggest remedial measure for prevention of suicide. Study Design: Retrospective study. Place and Duration of study: This study was carried out at the Department of Forensic Medicine, NMC Multan from 01-01-2007 to 31-12-2011 Materials and Methods: The study consisted of 90 cases of suicidal deaths declared as suicideon the information retrieved through psychological Autopsy belonging to both genders and different age groups, whose autopsy was conducted in the mortuary of department of Forensic Medicine, NMC Multan. Findings were recorded on the Performa and the results statistically analysed. Results: The study disclosed that suicidal rate was 1.22/100000 with male dominance. The most vulnerable age for suicide in male was 21-30 years and that for females was between 11-20 years. Hanging was the commonest method employed. Conclusion: The suicide is increasing in Multan and all over Pakistan and demands immediate intervention and remedial measures for its prevention.